Developing a learning management system for critical literacy course: A need analysis - Palupi, Tara Mustikaning (citeus, 2023)
In preparing the students to have the ability to interpret texts using critical lenses, to challenge the power relations within the messages and communicate actively in multimodal context, there is a need and urgency of the hybrid learning process to take place. As part of multi-years’ research and development which aims to develop digital module and learning management systems (LMS) for the students, this preliminary needs-based research focuses on the students’ and lecturers’ perceptions regarding the need for developing LMS in the Critical Literacy course in Bachelor of English Language Education, Universitas Negeri Jakarta. The research participants were thirty-two students, and a lecturer who responded to questionnaires, interviews to lecturer, and focus group discussions. The research data was the students’ needs based on Hutchinson and Water’s theory which could be divided into target needs (necessities, lacks and wants) and learning needs. The study was conducted with the qualitative approach with the Successive Approximation Model (SAM) which focuses on Preparation Phase research design. Throughout the information gathering and the Savvy Start, the phase rotated through needs analysis and library study. The results demonstrate that there is a gap between the expected outcomes of the Critical Literacy course and students' ability to understand various texts, especially in understanding the interpretation of data in the form of graphs, tables, and numbers. Also, students need exposure to various texts such as news items, critical analysis of texts, and current issues in education. While the difficulty experienced by lecturers when teaching is that students' language skills (especially reading) are very varied. Also, the lecturer and students want Critical Literacy material that makes students think critically about topics related to critical literacy theory, strategy, and its practice. The preferred activities in this course include debates, discussions, criticizing social campaigns, advertisements and short films, and topics on digital literacy. By this, developing a ready-to-use digital English learning materials that correspond to the students’ and lecturer’s is exigent.